Hybrid photovoltaic-triboelectric nanogenerators for simultaneously harvesting solar and mechanical energies. (November 2021) - Wu, Yinghong; Qu, Jingkui; Chu, Paul K.; Shin, Dong-Myeong; Luo, Yang; Feng, Shien-Ping
Abstract: Owing to its potential to maximize the power output, hybrid energy harvesting technology has attracted more research interest. Boosting merits such as renewable energy sources and high output, hybrid photovoltaic-triboelectric nanogenerator (HPTNG) is considered as one of the promising power sources for next-generation smart electronics. To date, there is still a lack of a comprehensive review of the latest development and challenges of HPTNGs. Herein, we systematically summarize the recent advances of the hybrid photovoltaic-triboelectric energy-harvesting system. In particular, the structural flexibility and simplification of the hybridized device is described, followed by the detailed discussion from perspectives of the input mechanical energy sources, the output interaction between triboelectric nanogenerators and solar cells, as well as the functions and applications of the HPTNGs. Finally, the main challenges and perspective for the future development of HPTNGs are discussed. Graphical Abstract: ga1 Highlights: Advances in hybrid photovoltaic-triboelectric nanogenerators is summarized. Structural flexibility and simplification of the hybridized device is described. HPTNGs are classified and descried according to mechanical energy sources. Effect of TENG on the performance of solar cells is systematically analyzed. Functions, applications, challenges and perspective of HPTNGs are discussed.